Correction: Insight into the relationship between redox ability and separation efficiency via the case of α-Bi2O3/Bi5NO3O7. Issue 20 (30th September 2022) - Li, Jie-hao; Liu, Rui-hong; Ning, Meng; Li, Yi-lei; Liu, Ying; Liu, Xinying; Khangale, Phathutshedzo; Hildebrandt, Diane; Wang, Xiao-jing; Li, Fa-tang
Abstract : Correction for 'Insight into the relationship between redox ability and separation efficiency via the case of α-Bi2 O3 /Bi5 NO3 O7 ' by Jie-hao Li et al., Inorg. Chem. Front., 2022, 9, 3578–3589, ; https://doi.org/10.1039/D2QI00731B .